2015
DOI: 10.1099/jgv.0.000004
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the functional sites in porcine reproductive and respiratory syndrome virus non-structural protein 10

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is prevalent throughout the world and has caused major economic losses to the pig industry. Arterivirus non-structural protein 10 (nsp10) is a superfamily 1 helicase participating in multiple processes of virus replication. PRRSV nsp10, however, has not yet been well characterized. In this study, a series of nsp10 mutants were constructed and analysed for functional sites of different enzymic activities. We found that nsp10 could bind both ssDNA and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The integrity of nsp10 is essential for its helicase properties and this was in line with the previous studies of Arterivirus nsp10, which showed that the ZBD was required for its helicase activity and involved in genome replication (Seybert et al 2000(Seybert et al , 2005. PRRSV nsp10 has ATPase activity and can unwind dsRNA and dsDNA in a 5´ to 3´ direction (Bautista et al 2002;Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The integrity of nsp10 is essential for its helicase properties and this was in line with the previous studies of Arterivirus nsp10, which showed that the ZBD was required for its helicase activity and involved in genome replication (Seybert et al 2000(Seybert et al , 2005. PRRSV nsp10 has ATPase activity and can unwind dsRNA and dsDNA in a 5´ to 3´ direction (Bautista et al 2002;Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, the C-terminal treble-clef zinc finger of EAV nsp10 is stabilized by multiple hydrogen-bonding interactions, while the corresponding zinc finger of PRRSV nsp10 is more flexible without such an extensive array of hydrogen bonds, suggesting that the C-terminal zinc-binding motif may have less effect on the enzymatic activities in PRRSV nsp10 than in EAV nsp10. This speculation is confirmed by previous mutagenesis studies that H44A of EAV nsp10 (ligand for Zn3) retained a limited level of ATPase and helicase activities while the mutations in the mutant variant H43A had no obvious influence on the enzymatic activities of PRRSV nsp10 [55,56]. Thirdly, the resolution of the crystals of full-length EAV nsp10 was poor after extensive optimization and diffracting crystals could only be obtained for a truncated form lacking the CTD.…”
Section: Discussionsupporting
confidence: 62%
“…The helicase domain of PRRSV nsp10 participates in multiple processes during virus replication (23). Cys25 and His32 in nsp10 are critical for nucleic acid binding and unwinding, and Ala227 plays an important role in helicase activity (24). nsp10 also contains a putative zinc finger region which is implicated in subgenomic mRNA synthesis and genome replication.…”
mentioning
confidence: 99%